Targeted Photodynamic Therapy: A Novel Approach to Abolition of Human Cancer Stem Cells - Anine Crous; Elvin Chizenga; Natasha Hodgkinson; Heidi Abrahamse (International Journal of Optics)
Cancer is a global burden that has prompted extensive research into prevention and treatment, over many decades. Scientific studies have shown that subset of cells within a tumour, known as cancer stem cells (CSCs), are responsible for tumourigenesis, metastasis, drug resistance, and recurrences. CSCs have characteristic features of enhanced self-renewal, proliferation, and limited but multidirectional differentiation capacity. The discovery of CSCs has initiated extensive research into novel cancer treatment regimes. Evidence indicates that CSCs are resistant to conventional chemo- and radiation therapy leading to treatment failures, cancer metastasis, secondary cancer formation, and relapse. Because of the observed phenomena in the course of cancer prognosis, a need for treatment modalities targeting CSCs is important. Photodynamic therapy (PDT) is a clinically approved, minimally invasive, therapeutic procedure that can exert a selective cytotoxic activity toward cancerous cells while reducing toxicity to normal cells. It uses a photosensitizer (PS) that becomes excited when subjected to light at a specific wavelength, and the PS forms reactive oxygen species (ROS) killing malignant cells. Currently, PDT is being investigated as a target specific treatment for CSCs by the addition of carrier molecules and antibody conjugates bound to the PS. Targeted PDT (TPDT) may be able to not only eradicate the tumour mass but kill CSCs as well.